The State of Public Service Delivery in Uganda: Report of a baseline survey - Kabunga, Nassul S.; Mogues, Tewodaj; Bizimungu, Emmanuel; Erman, Alvina; Van Campenhout, Bjorn (International Food Policy Research Institute, 2016)
This report describes the baseline data collected as part of a major impact evaluation of the Government of Uganda’s Community Advocacy Forum (Baraza) initiative. The Baraza initiative’s aims were to (1) strengthen governance and downward accountability within the public sector, and (2) ensure adequate space for ordinary citizens to participate in planning and monitoring of government services in their local communities. The International Initiative for Impact Evaluation (3ie) engaged the Kampala office of International Food Policy Research Institute (IFPRI), which proposed to assess the impact of the Baraza initiative with a mixed methods approach, using sufficient, representative, and temporal datasets to control for any biases and consistently estimate the impact of barazas in Uganda. A major component of the impact evaluation was a social experiment in the form of a clustered randomized controlled trial, for which a nationwide baseline survey was carried out in August 2015.